A Pan-Amazonian species delimitation: High species diversity within the genus Amazophrynella (Anura: Bufonidae) - Rojas R.R. (2018)
The effect of carboxymethylation and NH4I incorporation on the molecular dynamics of carrageenan films was studied. Broadband Dielectric Spectroscopy (BDS) assessed the presence of α and β relaxation processes. The effect of NH4I content was analyzed using the Havriliak-Negami model and parameterizing the temperature dependence of the relaxation times according to the Vogel-Fulcher-Tammann-Hesse (VFTH) equation. The glass transition temperature was found to decrease with the increase of NH4I content. These results suggest that carboxymethylation and the salt doping treatment increase the molecular mobility of NH4+ ions, making the films suitable for the development of solid electrolytes for energy storage applications. © 2018, © 2018 Taylor & Francis Group, LLC.